Improving mathematical reasoning ability through project-based learning in middle school classrooms - Prayekti, Novi (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This study explores the impact of project-based learning (PBL) on improving mathematical reasoning abilities in middle school classrooms. Utilizing a qualitative literature review methodology, the research synthesizes findings from a range of scholarly articles, educational reports, and case studies that investigate the effectiveness of PBL in enhancing students' mathematical skills. The review highlights the key characteristics of PBL, including its emphasis on real-world applications, collaborative learning environments, and student-centered approaches, which collectively foster deeper engagement and critical thinking in mathematics. Evidence from various studies indicates that PBL not only enhances students' understanding of mathematical concepts but also promotes their ability to reason mathematically, solve complex problems, and apply their knowledge in practical situations. Furthermore, the study examines the challenges and barriers educators face when implementing PBL, such as curriculum constraints and varying levels of student readiness. By identifying effective strategies for overcoming these challenges, the research provides valuable insights for educators seeking to integrate PBL into their mathematics instruction. Ultimately, this study underscores the potential of project-based learning as a transformative pedagogical approach that can significantly enhance mathematical reasoning abilities among middle school students, thus preparing them for future academic and real-world challenges.